Design and Development of an Electric Stove for Wood Powder Roasting using Fuzzy Logic - YAHYA CHUSNA ARIF; LUKI SEPTYA MAHENDRA; IZMI NURUL IZZAH; HENDIK EKO HADI SUHARYANTO; PUTU AGUS MAHADI PUTRA; LUCKY PRADIGTA SETIYA RAHARJA (Institut Teknologi Nasional, Bandung, 2025)
Kampung Seni Grajen utilizes this wood dust waste to create high-value paintings through a manual roasting process, which requires significant time and intensive supervision. This study aims to develop an electric stove based on fuzzy logic to improve the efficiency of the wood dust roasting process. The electric stove employs a Band Heater as a heating element, controlled by an AC-AC Controller and fuzzy logic to regulate the temperature automatically. The system is also equipped with an agitator to ensure even heat distribution. Testing was conducted using both open-loop and closed-loop methods. In the open-loop testing, the input voltage directly affected the temperature, but the temperature increase was not always linear. The closed-loop testing demonstrated that the system could maintain a stable temperature in the range of 84°C to 87°C, with an error rate of 2.38%, despite slight discrepancies due to environmental factors or sensor tolerances. The roasting results are used to make Grajen paintings